Rural Development Programme III: 1993-1995: project document - BRAC (© BRAC, 2016)
1. History of BRAC 2. Background of RDP I & II 3. The proposal 4. Institution building 5. Income and employment generation 6. Credit 7. Non formal primary education 8. IGVGD 9. Support service programmes 10. Gender and environment 11. Budget